The Contributions of Margaret Conrad to Public History in Canada - Dick, Lyle (Atlantis, 2010)
The presentation elaborates and assesses the contributions of Margaret Conrad to the field of public history in Canada. Throughout her career, she has been concerned with the relationship of the historical discipline to its diverse publics. By her example, she has shown how scholars from academic history backgrounds can more effectively engage public history, strengthening both the profession and the credibility of public representations of history.